Acceptability and feasibility of HIV self-testing integration into publicly-funded HIV prevention services: Perspectives from HIV testing agency staff that provide HIV testing services to sexual and gender minority youth in Philadelphia County - Dovie L. Watson; Stephen Bonett; Steven Meanley; Sarah M. Wood; Kathleen A. Brady; José A. Bauermeister (PLoS ONE, 2025)
Background Increasing HIV testing among priority populations is a primary strategy of the Ending the HIV Epidemic initiative. In October 2019, the Philadelphia Department of Public Health (PDPH) established a program to distribute publicly-funded HIV self-testing (HIVST) kits to Philadelphia County residents aged 16 years and older. Methods Through a community-academic partnership, we used a cross-sectional sequential transformative mixed-methods design to examine perceived organizational factors, opportunities, and challenges to HIVST integration among agency staff at PDPH-funded agencies early in the COVID-19 pandemic due to decreased access to traditional in-person HIV testing services with a focus on agencies whose client populations included sexual and gender minority clients assigned male sex birth aged 13 to 24 years (not the sole population served at each agency). We integrated data from online surveys conducted with HIV testers (test counselors and testing leads), agency leaders (agency leads and directors), and care navigators (n =  42), and semi-structured interviews with HIV testers and agency leaders (n =  11) employed at PDPH-funded agencies. Results Many staff were familiar with HIVST (79%), and approximately two-thirds (64%) were likely to encourage HIVST to clients. In interviews, perceived benefits of HIVST integration were increased access to HIV testing, accommodation for client privacy, decreased risk of stigmatizing encounters, and testing program adaptability. Perceived challenges were loss of connection with clients, suboptimal linkage to HIV treatment and prevention services after self-testing, concerns regarding clients’ correct use or interpretation of test results, and client preference. Conclusions Agency staff described HIVST as a useful tool for expanding low-barrier HIV testing services; however, staff foresaw potential implementation challenges. To optimize HIVST as a long-term strategy, resources are needed to increase familiarity and comfort with HIVST and enhance staff’s capacity to establish meaningful client connections and link clients to post-test HIV treatment and pre-exposure prophylaxis services.